Marsh Rams-Horn, Marsh Ramshorn Helisoma (Planorbella) trivolvis (Say) (Gastropoda: Planorbidae) - Carrie Suen; Jennifer Lynn Gillett-Kaufman (EDIS, 2019)
The marsh rams-horn, Helisoma (Planorbella) trivolvis (Say), is a species of air-breathing freshwater aquatic snail that is native to Florida. It belongs to the family Planorbidae, commonly known as the ramshorn snail, which comes from the shape of its shell. https://edis.ifas.ufl.edu/in1234